Hubungan Pola Interaksi Keluarga dan Perkembangan Kemampuan Pragmatik Anak Prasekolah di TKIT Insan Kamil Karanganyar - Budhi Astuti, Erlina; Dewi Syah Fitri, Anisyah (Jurnal Terapi Wicara dan Bahasa, 2023)
Background: Family interaction patterns are reciprocal relationships within a family that are deliberately built to influence, change, or improve behavior with social contact and communication between family members. Whether or not family interaction patterns are harmonious affects the development of language (including pragmatic language) and the child's social. Pragmatics is the ability to use language according to the context in social communication. Objectives: This study aims to determine the relationship between family interaction patterns and the development of pragmatic abilities of preschoolers in TKIT Insan Kamil Karanganyar. Methods: This research is a quantitative study with a cross-sectional research design. The sampling technique in this study was simple random sampling, with a total sample of 58 respondents. The collected data was tested using Pearson Product Moment. Results: Pearson Product Moment test results obtained a p value of 0.000, that is, if the p value < 0.05, then the alternative hypothesis (Ha) is accepted. The strength of the relationship can be seen from the result r = 0.880, the result shows a "very strong" correlation strength. Conclusion: There is a relationship between family interaction patterns and the development of pragmatic abilities of preschoolers in TKIT Insan Kamil Karanganyar. Keywords: Family Interaction Patterns, Development of Pragmatic Abilities, Preschoolers